The effect of pH of the sodium hypochlorite on smear layer removal - Karadžić Branislav; Dimitrijević Nina; Manojlović Dragica; Trišović Tomislav (Stomatološki glasnik Srbije, 2010)
Introduction. Canal irrigation is an important segment of endodontic treatment. The aim of this study was to assess the efficacy of 0.5% NaOCl solutions of different pH values on smear layer removal. Material and Methods. Thirty-two freshly extracted single rooted teeth with gangrenous pulp were used in the study. The samples were divided into four groups of eight teeth in each. Four solutions of 0.5% NaOCl having pH values 5, 7, 9 and 12 respectively, were used during chemomechanical instrumentation with hand instruments and using step back technique. SEM analysis was done to assess the quality of smear layer removal in apical, middle and coronal part of root canal. Presence and quantity of smear layer and detritus was quantified using the scale from 1 to 5. Results. SEM analysis results showed similar results for 0.5% NaOCl solutions of different pH values in root canal cleaning with no statistically significant differences. Conclusion. The most effective cleaning root canal was achieved with 0.5% NaOCl solution of pH 5.